2021
DOI: 10.31018/jans.v13i4.3145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drought on gas exchange and chlorophyll fluorescence of groundnut genotypes

Abstract: Drought is one of the major threats to groundnut productivity, causing a greater loss than any other abiotic factor. Water stress conditions alter plant photosynthetic activity, impacting future growth and assimilating mobilization towards sink tissues. The purpose of this study was to investigate how drought impacts the photosynthesis of plants and its links to drought tolerance. The influence of reproductive stage drought on photosynthetic activity and chlorophyll fluorescence of groundnut is well studied. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Drought induced root to leaf signaling resulted in stomatal closure through transpiration rate (Leal-Alvarado et al, 2016). Manojkumar et al (2021) revealed that the reduced stomatal conductance resulted in decreased lower net chloroplast carbondioxide tension and reduced the photosynthetic e ciency. Comparative impact of drought stress in rice physiology have been contemplated Ding et al (2014).…”
Section: Discussionmentioning
confidence: 99%
“…Drought induced root to leaf signaling resulted in stomatal closure through transpiration rate (Leal-Alvarado et al, 2016). Manojkumar et al (2021) revealed that the reduced stomatal conductance resulted in decreased lower net chloroplast carbondioxide tension and reduced the photosynthetic e ciency. Comparative impact of drought stress in rice physiology have been contemplated Ding et al (2014).…”
Section: Discussionmentioning
confidence: 99%